2020
DOI: 10.1111/bju.15126
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features and predictive factors of nocturnal enuresis in adult men

Abstract: To characterise the clinical features and to discover predictive factors of adult males with nocturnal enuresis (NE). Patients and Methods A total of 43 eligible adult male patients (mean age was 57.8 years) were recruited prospectively over a 2-year period. After documentation of medical history, lower urinary tract symptoms (LUTS) were assessed using the International Consultation on Incontinence Modular Questionnaire-male LUTS (ICIQ-MLUTS), and a 3-day ICIQ-bladder diary (ICIQ-BD). Videourodynamic studies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…There is a relatively high percentage of women with increased BMI (≥24 kg/m 2 ), which is associated with more frequent NE, consistently with our findings from that in men and reports from Song et al ( 6 ) and Madhu et al ( 18 ). As to the causes of secondary NE, we found that 11 out of 70 women had previous hysterectomy, although surgical onset only serves as a risk factor for NE episodes in the univariate analysis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…There is a relatively high percentage of women with increased BMI (≥24 kg/m 2 ), which is associated with more frequent NE, consistently with our findings from that in men and reports from Song et al ( 6 ) and Madhu et al ( 18 ). As to the causes of secondary NE, we found that 11 out of 70 women had previous hysterectomy, although surgical onset only serves as a risk factor for NE episodes in the univariate analysis.…”
Section: Discussionsupporting
confidence: 93%
“…The overall incidence of daytime incontinence was 64.3% in women with NE, with 41.4% suffering from SUI, which was unsurprisingly higher than that in men due to gender difference ( 6 ). Importantly, we further corroborated that incontinence-related subjective symptom scores on ICIQ-FLUTS and USI are independent predictors for NE frequency ( 18 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations